« It starts when you begin to overlook good manners. Any time you quit hearin Sir and Mam the end is pretty much in sight » : la jérémiade dans No Country for Old Men - François Gavillon (Revue LISA)
Is it legitimate to read in the old sheriff Ed Tom Bell’s ruminations the modern accents of an ancient form, that of the jeremiad? This is what Jay Ellis suggests in an article entitled “Fetish and Collapse in No Country for Old Men”. Taking its cue from this suggestion, this article proposes to trace the historic precedents of the jeremiad, from its biblical origins to its renaissance in 17th-century Puritan New England. Chronically, the jeremiad has revealed individual as well as collective aspirations for moral, religious, civil and political perfection. It has no less emphatically described the just retributions that divine wrath rains on apostates and sinful communities. It does seem that Cormac McCarthy draws upon the jeremianic tradition, the question being how, and to what novelistic – commentarial, choral, prophetic, philosophical, or simply compositional – ends?